2019
DOI: 10.1111/bph.14801
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological basis and new insights of resveratrol action in the cardiovascular system

Abstract: Resveratrol (trans‐3,4′,5‐trihydroxystilbene) belongs to the family of natural phytoalexins. Resveratrol first came to our attention in 1992, following reports of the cardioprotective effects of red wine. Thereafter, resveratrol was shown to exert antioxidant, anti‐inflammatory, anti‐proliferative, and angio‐regulatory effects against atherosclerosis, ischaemia, and cardiomyopathy. This article critically reviews the current findings on the molecular basis of resveratrol‐mediated cardiovascular benefits, summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 155 publications
(187 reference statements)
1
63
0
1
Order By: Relevance
“…Regarding phenolic constituents, or polyphenols, also present in fruit, grains, and vegetables, data from several studies suggest that they have healthy properties [ 1 , 6 , 7 , 8 ]. Resveratrol, a non-flavonoid present in trace quantities, is a natural antioxidant and anti-inflammatory compound, known to play a key role in immunoregulation, metabolic syndrome, cardiovascular, neuroprotection, and cancer treatment [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. It has also received attention due to its antimicrobial activity against bacterial, fungal, and viral species in vitro [ 21 , 22 , 23 , 24 ].…”
Section: Introduction: An Overview Of Wine To the Past From The Prmentioning
confidence: 99%
“…Regarding phenolic constituents, or polyphenols, also present in fruit, grains, and vegetables, data from several studies suggest that they have healthy properties [ 1 , 6 , 7 , 8 ]. Resveratrol, a non-flavonoid present in trace quantities, is a natural antioxidant and anti-inflammatory compound, known to play a key role in immunoregulation, metabolic syndrome, cardiovascular, neuroprotection, and cancer treatment [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. It has also received attention due to its antimicrobial activity against bacterial, fungal, and viral species in vitro [ 21 , 22 , 23 , 24 ].…”
Section: Introduction: An Overview Of Wine To the Past From The Prmentioning
confidence: 99%
“…Despite sharing some biochemical pathways and molecular targets, the physiological effects of rhaponticin and rhapontigenin still remain poorly understood, when compared to the current knowledge of biological actions of resveratrol. Accumulating evidence from in vitro and in vivo investigations has indicated that resveratrol displays a wide range of beneficial properties such as antioxidant, cardioprotective, anticancer, neuroprotective and anti-inflammatory action (see Cheng et al 2019;Ramírez-Garza et al 2018). Resveratrol may interact with different targets and modulate the activities of numerous pro-inflammatory mediators through the inhibition of the nuclear factor kappa B (NF-jB) activation, reduction of inflammatory cytokine levels and iNOS activity as well as Similarly to resveratrol, the anti-inflammatory action of rhaponticin and rhapontigenin also involves the inhibition of the activation of NF-jB.…”
Section: Anti-inflammatory Action Of Rhaponticin and Rhapontigeninmentioning
confidence: 99%
“…The stilbenoids are a well-known group of bioactive phytochemicals, that are synthesized by various plant species and accumulated in aerial and underground plant organs. Although resveratrol still remains the best described stilbene (see Cheng et al 2019;Ramírez-Garza et al 2018), it should be noted that this class of polyphenols includes many other bioactive compounds, such as rhapontigenin and rhaponticin, which display a wide range of beneficial activities, including antioxidant, estrogenic, antithrombotic, anticancer and anti-inflammatory effects (see Czop et al 2019;Kim and Ma 2018;Park et al 2002;Sun et al 2017;Wober et al 2007;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al Cardiovasc Diabetol (2020) 19:33 cholesterol metabolism (SREBP-2) and fatty acid synthesis (SREBP-1c) [4]. Resveratrol is a polyphenolic compound that protects against atherosclerosis [5]. Jing et al [6] found that hepatic PCSK9 expression could be attenuated by resveratrol via downregulating the expression of SREBP-1c.…”
Section: Introductionmentioning
confidence: 99%